Sensitive and specific serodiagnosis of tegumentary leishmaniasis using a new chimeric protein based on specific B-cell epitopes of Leishmania antigenic proteins. (January 2022) - Galvani, Nathalia C.; Machado, Amanda S.; Lage, Daniela P.; Martins, Vívian T.; de Oliveira, Daysiane; Freitas, Camila S.; Vale, Danniele L.; Fernandes, Bruna B.; Oliveira-da-Silva, João A.; Reis, Thiago A.R.; Santos, Thaís T.O.; Ramos, Fernanda F.; et al.
Abstract: Serological tests used for the diagnosis of tegumentary leishmaniasis (TL) presents problems, mainly related to their variable sensitivity and/or specificity, which can be caused by low levels of antileishmanial antibodies or by presence of cross-reactive diseases, respectively. In this context, the search for new antigenic candidates presenting higher sensitivity and specificity is urgently required. In the present study, the amino acid sequences of the LiHyT, LiHyD, LiHyV, and LiHyP proteins, which were previously showed to be antigenic in the visceral leishmaniasis (VL), were evaluated and eight B-cell epitopes were predicted and used for construction of gene codifying a chimeric protein called ChimLeish. The protein was expressed, purified and evaluated as a recombinant antigen in ELISA (Enzyme-Linked Immunosorbent Assay) for the diagnosis of TL. The own B cell epitopes used to construct the chimera were synthetized and also evaluated as antigens, as well as a soluble Leishmania braziliensis antigenic extract (SLA). Results showed that ChimLeish presented 100% sensitivity and specificity to diagnose TL, while synthetic peptides showed sensitivity varying from 9.1% to 90.9%, while specificity reached from 98.3% to 99.1%. SLA showed sensitivity and specificity of 18.2% and 98.3%, respectively. A preliminary prognostic evaluation showed that anti-ChimLeish IgG antibodies declined in significant levels, when serological reactivity was compared before and six months after treatment, suggesting also a possible prognostic role of this antigen for TL. Graphical abstract: Image 1 Highlights: Bioinformatics assays identified eight conserved B-cell epitopes of Leishmania proteins. They were grouped and composed the sequence of a chimeric protein. Both peptides and protein were tested for diagnosis of tegumentary leishmaniasis. High sensitivity and specificity values were found for the recombinant chimera. The chimera showed potential prognostic action for tegumentary leishmaniasis.